Pemberdayaan Kader dalam Penanganan Kasus Keracunan di Desa Wisata Lebak Muncang, Ciwidey, Kabupaten Bandung: Empowerment of Cadres in Handling Poisoning Cases in Lebak Muncang Tourism Village, Ciwidey, Bandung Regency - Zakiyah, Zakiyah; Pamungkas, Indra Gilang; Rahmawati, Apriana; Marianna, Siswani; Setyaningsih, Widanarti; Wulandari, Cyntia (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Poisoning is one of the conditions that can occur in a tourist village. Handling or first aid for poisoning problems needs to be carried out by tourism service providers or the community. Providing education and also empowerment can be done with the hope of increasing knowledge about first aid that must be done in cases of poisoning in the Tourism Village. This community service is carried out to increase the knowledge of cadres and the community in handling poisoning cases through empowerment. Community service is carried out by applying empowerment to cadres on 5 topics such as handling cases of respiratory allergies, handling cases of pesticide poisoning, handling cases of food poisoning, handling cases of venomous animal bites, introducing types of antidotes for poisoning and animal bites with local wisdom. The cadres' knowledge increased between before and after health education with a mean difference of 9 points from 77 to 86. Continuous activities are needed to maintain cadres' knowledge in handling poisoning cases.